A Comparative Study on The Efficiency of Genomic DNA Extraction Protocols for P53 Gene Polymorphism in Prostate Cancer - Zaizafoon Nabeel Nasif (Microbiology and Biotechnology Research: An Overview Vol. 2, 2025)
The physical, chemical, and physiological makeup of the prostate varies greatly between species. The prostate’s job is to emit a milky or white fluid that is slightly alkaline and accounts for around 30% of the amount of semen in humans, together with sperm cells and seminal vesicle fluid. Prostate cancer (PC), a type of cancer that develops in the prostate gland in the male reproductive system, is one of the most prevalent cancers influencing older men in the developed world and a major inducer of mortality for elderly men. In recent decades, genetic techniques have emerged as a powerful resource across various life-related applications. DNA-based technologies, such as PCR, are increasingly utilized in research focused on demographic genetic diversity, QTL detection, marker-assisted selection, and food traceability. These methodologies necessitate extraction processes that ensure effective nucleic acid retrieval and the removal of PCR inhibitors. The initial and most critical step in molecular biology is the extraction of DNA from cells. For molecular scientists, the quality and integrity of the isolated DNA, along with the extraction method’s user-friendliness and cost-effectiveness, are essential considerations. This study aimed to develop a straightforward, rapid, and cost-effective technique for extracting DNA from human peripheral blood samples, specifically comparing two normal male subjects aged 24 years (n=2) and two male patients with prostate cancer aged 65 years (n=2). The objective was to standardize a DNA extraction protocol utilizing five different extraction methods. The first method involved a modified organic approach that substituted sodium perchlorate for traditional organic solvents like phenol and chloroform, highlighting the advantages of sodium perchlorate due to its affordability and minimal storage and shipping requirements. The second method employed an enzymatic approach using proteinase K, while the third method utilized a detergent. The fourth method incorporated phenol chloroform, and the final method was based on the salting out technique. The findings indicated that the organic extraction method produces a satisfactory yield of DNA in a relatively brief period, while the enzymatic extraction method results in superior DNA purity, making it more appropriate for PCR applications. The purpose of the present study was to find a suitable procedure for DNA extraction with low cost, time, and hazards as well as high yield, purity, and excitability for PCR amplification. Among the primary strategies for obtaining DNA is from whole blood specimens, and there are a variety of protocols known to extract nucleic acids from such specimens. The five proposed methods for DNA extraction significantly lower costs by utilizing only basic and easily obtainable laboratory supplies and equipment, eliminating the need for expensive components such as K and RNase proteins. This conclusion was drawn from a comparison of five different protocols utilizing spectrophotometry, Nanodrop technology, and electrophoresis. The PCR amplification of the P53 gene using the isolated DNA was successfully achieved through these five methods. This suggests that, apart from the detergent-based method, there were no significant inhibitors present for Taq polymerase in the final solution.